Perceived Organizational Creative Climate In Determining The Work Innovativeness Among Information Technology Engineers In Taiwan : Knowledge Acquisition Capability As A Mediator - Ho, Mei Yan (2014)
The purposes of this study were to (i) examine the direct effect of organizational acquisition capability serves as a mediator in the above direct relationship. Work innovativeness and knowledge acquisition capability were conceptualized as unidimension. Organizational creative climate consists often dimensions: freedom, idea support, trust/openness, playfulness/humour. idea time. challenge. dynamism/liveliness, debates. conflicts and risk taking. The hypothesized relationships were tested using a sample of 253 respondents. The SPSS and SmartPLS (Partial Least Square) software were used for data analysis. The findings revealed that idea support. trust/openness, playfulness/humour and idea time) had significant positive influence whereas another five dimensions (challenge, dynamism/liveliness. debates, conflicts and risk taking) were not significant with work innovativeness and knowledge acquisition capability. Besides, the knowledge acquisition capability was found to be significant positively related to the work innovativeness. Knowledge acquisition capability was significantly mediated on the direct relationships between freedom and work innovativeness; idea support and work innovativeness; trust/openness and work innovativeness; playfulness/humour and work innovativeness; and idea time and work suggestions for future studies are also discussed.